IJCM_237A: Assessment of out-of-pocket expenditure amongst admitted patients in a tertiary care centre of Maharashtra: a cross-sectional study. - Ghoshal Titas; Gattani P. L.; Maidapwad S. L. (Wolters Kluwer Medknow Publications, 2024)
Background: In India, financing health-care majorly constitutes out-of-pocket expenditure. Health expenditure in India accounts for Objectives: 1. To assess the total out-of-pocket expenditure of patients due to current illness. 2. To assess out-of-pocket health expenditures in a single episode of illness in families of different socio-economic strata. 3. To study association between various specialities and direct out-of-pocket health expenditure incurred after admission. 4. To find the percentage of patients getting benefit of state government health insurance (MJPJAY). Methodology: A cross-sectional study was conducted by interviewing 233 patients (or care-takers) admitted in a tertiary-care centre, using a pre-designed semi-structured questionnaire in local language. Expenditures before and after admission (=3 days) due to current illness was documented. Enrolment for MJPJAY benefit was recorded. The data was compiled in MS-excel and analysed using SPSS. Results: The median out-of-pocket expenditure for the current illness was Rs.2935 (IQR: Rs.1375 to Rs.8508.75). The median out-of-pocket expenditure in the IVth and Vth social classes according to Modified B.G. Prasad classification, is Rs.3715(IQR: Rs1925 to Rs.9060) and Rs.5210(IQR: Rs.2917 to Rs.8350) respectively. 12.43% (excluding obstetric) patients were enrolled for benefit of MJPJAY at the time of study. Conclusion: The out-of-pocket expenditure is found to be high among the patients studied, especially, among those choosing to visit private health facilities pre-admission. Post-admission, as the direct expenditure was more than indirect in most cases, the underlying causes may be unavailability of drugs and investigations required for management. MJPJAY benefits are received post diagnosis, therefore pre-diagnostic investigations contribute to high out-of-pocket expenses. Further studies are required to evaluate the preference towards private health facility.